Anti-osteogenic activity of cadmium in zebrafish - Tarasco, Marco (2020)
Among the many anthropogenic chemicals that end up in the aquatic ecosystem, heavy metals, in particular cadmium, are hazardous compounds that have been shown to affect developmental, reproductive, hepatic, hematological, and immunological functions in teleost fish. There is also evidence that cadmium disturbs bone formation and skeletal development, but data is scarce. In this work, zebrafish was used to further characterize the anti-osteogenic/osteotoxic effects of cadmium and gain insights into underlying mechanisms. Upon exposure to cadmium, a reduction of the opercular bone growth was observed in 6-days post-fertilization (dpf) larvae and an increase in the incidence of skeletal deformities was evidenced in 20-dpf post-larvae. The extent and stiffness of newly formed bone was also affected in adult zebrafish exposed to cadmium while regenerating their caudal fin. A pathway reporter assay revealed a possible role of the MTF-1 and cAMP/PKA signaling pathways in mechanisms of cadmium osteotoxicity, while the expression of genes involved in osteoblast differentiation and matrix production was strongly reduced in cadmium-exposed post-larvae. This work not only confirmed cadmium anti-osteogenic activity and identified targeted pathways and genes, but it also suggested that cadmium may affect biomechanical properties of bone.